The Evaluation of Difficult Intubation Risk in Children with Hydrocephalus Undergoing Shunt Surgery: A Prospective Controlled Study - (:unkn) unknown (My University, 2020)
INTRODUCTION: Hydrocephalus commonly cause seriouschallenges in airway management of newborn and paediatricpatients, leading to enlarged head and distortion of skullanatomy. This result in difficulty for conventionallaryngoscopy by hindering positioning of head. In this study,we aimed to determine the relationship between anatomicfeatures and the signs of difficult intubation in paediatricpatients undergoing shunt surgery.METHODS: Sixty patients requiring ventriculoperitonealshunt insertion were enrolled. Patients divided into threegroups based on >1 month of age with hydrocephalus (n=20),newborn with hydrocephalus (n=20) and newborn withouthydrocephalus (n=20). Head circumference, the lower andupper lip-chin distance, sternomental and thyromentaldistance, Cormack-Lehane Classification scores wererecorded. The number of attempts for successful intubation,presence of optimization maneuvers were also recorded. Thedifficulty of intubation was evaluated with a 10 cm VAS ruler.All patients were intubated by the same anaesthesiologist.RESULTS: The ASA scores, number of intubation attempts,and the frequency of optimization maneuvers were significantlylower in neonates without hydrocephalus as compared topatients with hydrocephalus (p˂0.05). The tragus-to-chindistance was decreased in the neonates with hydrocephalus incomparison with those without hydrocephalus. The CormackLehane grade III was significantly increased while theCormack-Lehane grade I was significantly decreased inneonates with hydrocephalus (p<0.05). Whereas 45% of theneonates with hydrocephalus were intubated at the secondattempt, the rate was only 10% in control group.DISCUSSION AND CONCLUSION: The results of this studysuggest that the risk of difficult intubation increases inpaediatric patients with hydrocephalus.

GİRİŞ ve AMAÇ: Hidrosefali kafa kaidesinde genişlemeye ve kafatasının anatomisinin bozulmasına öncülük ederek genellikle yenidoğan ve pediatrik hastaların havayolu yönetiminde ciddi zorluklara neden olmaktadır. Bu, başın yerleşmesini engelleyerek geleneksel laringoskopi için zorlukla sonuçlanır. Bu çalışmada şant cerrahisi geçiren pediyatrik hastalarda anatomik özellikler ile zor entübasyon bulguları arasındaki ilişkiyi belirlemeyi amaçladık. YÖNTEM ve GEREÇLER: Ventriküloperitoneal şant yerleştirilmesi gerektiren altmış hasta çalışmaya alındı. Hastalar üç gruba ayrıldı: hidrosefalisi olan >1 ay üzerinde (n=20), hidrosefalisi olan yenidoğan (n=20) ve hidrosefalisi olmayan yenidoğan (n=20). Baş çevresi, alt ve üst dudak-çene mesafesi, sternomental ve tiromental mesafe, Cormack-Lehane sınıflaması skoru kaydedildi. Başarılı entübasyon için girişim sayısı, optimizasyon manevralarının varlığı da kaydedildi. Entübasyonun zorluğu 10 cm’lik VAS cetveliyle ölçüldü. Tüm hastalar aynı anesteziyolojist tarafından entübe edildi. BULGULAR: ASA skorları, entübasyon girişim sayıları, optimizasyon manevralarının sıklığı, hidrosefalisi olanlarla karşılaştırıldığında hidrosefalisi olmayan yenidoğanlarda anlamlı olarak daha düşüktü (p˂0,05). Hidrosefalisi olmayanlarla karşılaştırıldığında tragus-çene mesafesi hidrosefalisi olan yenidoğanlarda azalmıştı. Hidrosefalisi olan yenidoğanlarda Cormack-Lehane sınıf III anlamlı olarak artmışken, Cormack-Lehane sınıf I anlamlı olarak azalmıştır (p<0.05). Hidrosefalisi olan yenidoğanların ikinci girişimde entübasyon oranı %45 iken bu oran kontrol grubunda sadece %10’du. TARTIŞMA ve SONUÇ: Bu çalışmanın sonuçları hidrosefalisi olan çocuk hastalarda zor entübasyon riskinin arttığını göstermektedir.
Şant Cerrahisi Geçiren Hidrosefalili Çocuklarda Zor Entübasyon Riskinin Değerlendirilmesi: Bir Prospektif Kontrollü Çalışma